Investigating the dental toolkit of primates based on food mechanical properties: Feeding action does matter. Issue 6 (2nd February 2017) - Thiery, Ghislain; Guy, Franck; Lazzari, Vincent
Abstract : Although conveying an indisputable morphological and behavioral signal, traditional dietary categories such as frugivorous or folivorous tend to group a wide range of food mechanical properties together. Because food/tooth interactions are mostly mechanical, it seems relevant to investigate the dental morphology of primates based on mechanical categories. However, existing mechanical categories classify food by its properties but cannot be used as factors to classify primate dietary habits. This comes from the fact that one primate species might be adapted to a wide range of food mechanical properties. To tackle this issue, what follows is an original framework based on action‐related categories. The proposal here is to classify extant primates based on the range of food mechanical properties they can process through one given action. The resulting categories can be used as factors to investigate the dental tools available to primates. Furthermore, cracking, grinding, and shearing categories assigned depending on the hardness and the toughness of food are shown to be supported by morphological data (3D relative enamel thickness) and topographic data (relief index, occlusal complexity, and Dirichlet normal energy). Inferring food mechanical properties from dental morphology is especially relevant for the study of extinct primates, which are mainly documented by dental remains. Hence, we use action‐related categories to investigate the molar morphology of an extinct colobine monkey Mesopithecus pentelicus from the Miocene of Pikermi, Greece. Action‐related categories show contrasting results compared with classical categories and give us new insights into the dietary adaptations of this extinct primate. Finally, we provide some possible directions for future research aiming to test action‐related categories. In particular, we suggest acquiring more data on mechanically challenging fallback foods and advocate the use of other food mechanical properties such as abrasiveness. The development of new action‐related dental metrics is also crucial for primate dental studies.